The Usage of Civil Engineering Analysis in Order to Improve Cost and Material Management of Public Boarding School Rumah Tahfiz in Jalan Tembung - Sheila_hani (Journal of Saintech Transfer, 2020)
In the construction of structures, cost is one of the factors that support success. Cost is very important to meet all the needs of work ranging from material procurement to labor. For this reason, civil engineering analysis needs to be done to produce work cost planning as an initial guide in calculating building budget costs that include material, labor and unit price. In the civil engineering analysis of the the two-story building of Rumah Tahfiz, there were various kinds of structural works ranging from foundations to roofs, and also finishing in the form of floors to windows. Those work items make reading work design activities more complex. For this reason, the Tahfiz House Foundation requires the assistance of engineers in analyzing the drawing design, producing more reasonable material calculations and building costs using their own estimated price calculations. From the design analysis activities, Rumah Tahfiz Foundation can find out the details of building activities, materials used, and the cost requirements per section of structural work, aimed at measuring the cost needs until the structure was completed. The help of Civil engineering analysis on the building simplify Rumah Tahfiz foundation in understanding and implementing building process which have a sustainable impact on financial management for future operational learning activites